'Bad language' in the Nordics: profanity and gender in a social media corpus. Issue 1 (2nd January 2021) - Coats, Steven
ABSTRACT: This study looks at the relative frequency of 'bad language' according to gender in Nordic languages and in English in a 210-million-token corpus of messages by 18, 686 Nordic Twitter users. For the Nordic languages, more than 19, 000 'bad-language' word forms were compiled on the basis of usage note annotations in major Nordic-language dictionaries. The most frequent terms overall are swear words, and while males use more of these items on average, the gender difference is less pronounced for English words. For potentially offensive words in the Nordic languages, males make more use of traditional profanities associated with the Devil, religion, and blasphemy. Both genders make more use of profanities when tweeting to people of their own gender. The study provides empirical evidence for a small gender-based discrepancy in the use of profanity in social media in the Nordic languages, mirroring results previously found in corpus-based studies of English-language data. The results are interpreted in light of previous findings as evidence for a gendered difference in sensitivity toward the use of language that could potentially be offensive.